Black sails. The complete first season [videorecording (DVD)] - Marshall, Neil, 1970-; Miller, Sam, 1962 September 28-; Stephens, Toby, 1969-; Kennedy, Jessica Parker; Arnold, Luke; Stevenson, Robert Louis, 1850-1894 ([publisher not identified], 2015)
With the help of the daughter of a local kingpin, Captain Flint and his men attempt to fight off the British Navy.